Penerjemahan Pronomina Persona Bahasa Jepang pada Takarir Bahasa Indonesia Anime Tada Never Falls in Love - Fahri Delfariyadi; Siti Shafa Febriani Aryanto (Universitas Sebelas Maret, 2023)
Personal pronouns are one of the characteristics that distinguishes each language from others. Personal pronouns are linguistic elements that refer to self-referential words. Personal pronouns in Japanese are classified into three types: first-person pronouns, second-person pronouns, and third-person pronouns. Personal pronouns are increasingly being studied not only in linguistics but also in applied linguistics, such as translation studies. Subtitles are used in audiovisual media translation. This research deals at how Japanese personal pronouns are translated into Indonesian subtitles of Yoshiko Nakamura's anime Tada Never Falls in Love. This study utilized two methods, namely data collection and data analysis. The translational equivalent method has been used in this study. Based on the findings, it is possible to conclude that personal pronouns in both the source and target languages have the same meaning components. There are, however, differences in the